Neurologic psychiatric syndromes in focus - Bogousslavsky, Julien 1954- (Frontiers of neurology and neuroscience / series editor J. Bogousslavsky, 2018)
After a period in which neurology and psychiatry have become more and more defined, neurologists' interest in psychiatric topics, and vice versa, has increased. This book provides readers with an overview of the most representative neuropsychiatric syndromes such as Ganser and Capgras syndromes. It fills an existing gap in current literature and reintroduces a clinical approach. Additionally, there is a historical perspective throughout time with a focus on the most relevant clinical syndromes, offering distinct value to readers. With this approach, the book serves as a useful and stimulating guide on the diagnosis and management of neurologic psychiatric syndromes. It is for neurologists, neurosurgeons, psychiatrists, and all others interested in neuropsychiatric topics because these syndromes also called 'uncommon' may in fact be more frequent than the literature suggests.